Phagocytic activity of blood neutrophils and its relationship with plasma concentration of TNF-Î±, IL-6 and milk SCC in crossbred cows during early lactation - Kaswan, Sandeep; Mukherjee, Joydeep; Prasad, Shiv; Dang, A K (The Indian Journal of Animal Sciences, 2012)
To study the inter-relationship between plasma concentrations of tumour necrosis factor-a (TNF-Î±) and interleukin- 6 (IL-6) with somatic cell count (SCC) and phagocytic activity (PA) of blood neutrophils, blood and milk samples were collected from 16 Karan Fries (KF) cows (8 high producing and 8 low producing) during 75 days of early lactation and from 4 mastitic KF cows during different days of clinical mastitis. PA of blood neutrophils was estimated by nitroblue tetrazolium (NBT) reductive assay. Plasma TNF-Î± concentration was highest on the day of calving (1.52 ng/ml) and it declined significantly in low yielding cows up to 45th day (0.44 ng/ml), whereas, it declined nonsignificantly in high yielding cows. Peak values of IL-6 were obtained at calving and during peak yield in low yielding cows, whereas, in high yielding cows, peak values were obtained towards peak yield only. PA was lowest at calving in both the group of cows and then increased significantly to normalize with the progression of lactation. Plasma concentration of cytokines TNF-Î± and IL-6 were significantly higher in mastitic animals as compared to normal animals. Significantly higher concentration of both the cytokines were observed during the first day (TNF-Î±, 2.09 ng/ml; IL-6, 26.2 ng/ml) of mastitis which later declined by the fifth day (TNF-Î±, 0.59 ng/ml; IL-6, 13.91 ng/ml) of mastitis. PA of blood neutrophils was lowest (0.15) on day 1 of mastitis and increased significantly by the fifth day (0.31) of mastitis. Plasma concentrations of IL-6, TNF-Î± and milk SCC during different days of mastitis were negatively correlated with PA of blood neutrophils. This study indicated that the plasma concentration of TNF-Î± and IL-6 can be used as an indicator of mammary stress around calving in high producing cows.